2022
DOI: 10.1016/j.telpol.2021.102241
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of internet use by school-age children: The challenges for Mexico during the COVID-19 pandemic

Abstract: The COVID-19 pandemic has further highlighted the deep digital divide in Mexico and the enormous challenge faced by its education system in continuing to educate the country's students while under confinement. The objective of this article was to examine the determinants of internet acces s, use and productive uses for school-age children in households of different socioeconomic levels. The Heckman selection model was estimated based on data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 57 publications
1
12
0
5
Order By: Relevance
“…Authors [ 33 ] observed a significant increase in the excessive use of technological media, which led to many situations of children with sleep disorders. The results of Martínez-Domínguez and Fierros-González [ 15 ] showed that the probability of having children with Internet access and use patterns depended on the level of schooling and economic situation of the parents, digital skills and place of residence, as well as the presence of Internet devices. These findings suggest the urgent need to redesign the current policy for the use of technological media with a comprehensive long-term vision that guarantees access to new technologies and their productive use for students immersed in an ecosystem of educational innovation for the next century.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors [ 33 ] observed a significant increase in the excessive use of technological media, which led to many situations of children with sleep disorders. The results of Martínez-Domínguez and Fierros-González [ 15 ] showed that the probability of having children with Internet access and use patterns depended on the level of schooling and economic situation of the parents, digital skills and place of residence, as well as the presence of Internet devices. These findings suggest the urgent need to redesign the current policy for the use of technological media with a comprehensive long-term vision that guarantees access to new technologies and their productive use for students immersed in an ecosystem of educational innovation for the next century.…”
Section: Discussionmentioning
confidence: 99%
“…Since COVID-19 dramatically changed human social life, restrictive lockdown periods to curb the spread of the virus were found to particularly affect the psychological well-being of children and their families [ 13 ]. For its part, technological media are present in many homes establishing changes in social communication and lifestyle [ 14 ]; however, the COVID-19 pandemic has further highlighted the deep digital divide and the enormous challenge its education system faces in continuing to teach students during the lockdown [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…They find that there is a negative relationship between Internet access and education inequality and that socioeconomic attributes such as the level of education and the distribution of formal education are important variables in explaining Internet access. Martinez-Dominguez and Fierros-Gonzales (2022) analyze the determinant of Internet access for school-age children in Mexico. They show that Internet access and usage patterns base on the level of education, socioeconomic status, digital skill, and the existence of electronic devices in the household.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…En México, las investigaciones sobre la brecha digital muestran indicadores sociodemográficos y económicos como el ingreso, el género, la edad, el nivel educativo y la ubicación geográfica para explicar el acceso, el uso y sus beneficios (Martínez-Domínguez y Fierros-González, 2021;Grishchenko, 2020;Scheerder, Van Deursen y Van Dijk, 2017). Entre los hogares, las diferencias en la adopción de las TIC se deben principalmente a factores económicos, sociales y demográficos (Ovando y Olivera, 2018).…”
Section: Brecha Digital Y Alfabetización Digitalunclassified